(untitled) (Plant Tissue Culture and Biotechnology, 2022)
Axillary bud explants of Oxalis corniculta grown in the field were excised and inoculated on MS medium with various concentrations and combinations of auxins (2, 4-D and NAA) and cytokinins (BAP and Kn) for indirect shoot formation through callus induction. Indirect organogenesis was achieved by the application of PGRs such as BAP, Kn, and NAA in the culture medium. The maximum mean shoot number (9.2) and regeneration frequency (77%) was found with BAP (2.0 mg/l) and NAA (0.5 mg/l). Healthy microshoots were separated and transferred to rooting medium supplemented with NAA, IBA and IAA. MS medium augmented with NAA 2.0 mg/l was found to be best for rooting. The regenerated plantlets were then hardened, acclimatized and where exhibited 75% survivability. The reproducible protocol can be used for regeneration and genetic transformation studies. Plant Tissue Cult. & Biotech. 32(2): 181-191, 2022 (December)